hi there,
i have a question on diagramming multiple conditionals: e.g., Q#15, section 1 of PT
#63 (june 2011), choice B states, "if someone tells the same lie to two different people, then neither of those lied to is owed an apology unless both are." i know this is not the correct answer choice but i had a question as to how we'd diagram a multi-part conditional statement like this. would the correct way be:
someone tells the same lie to two different people --> (at least one owed apology --> both owed apology)? if so, what would be the contrapositive of the entire sentence? i never dealt with a conditional within a conditional so any advice you have would be greatly appreciated!
thanks in advance!
Comments
The contrapositive would be if you negate the second condition, contradicting the truth of the condition. According to the second condition, if you must apologize to someone, you must apologize to both. If you can prove a situation where you must apologize to someone, but not necessarily both, then it cannot have been an apology for an identical lie told to two people.
If you can contradict the truth of the second condition, then the first condition could not have existed.
I hope I wasn't confusing.
given: "someone tells the same lie to two different people --> (at least one owed apology --> both owed apology)"
contrapositive: someone tells the same lie to two different people --> (both not owed apology --> neither owed apology)
and this is because the negation of a conditional, A --> B is A -->~B, correct?
It follows the same method as a normal condition:
Normal condition: A --> B
Negation: ~B --> ~A
Double conditional: A --> (C --> D)
Negation: First show we are discussing case where C-->D doesn't apply (i.e. C-->~D or ~D-->C). Once the (C-->D) rule is inapplicable, A must be as well.
There's a lesson on embedded conditionals:
http://7sage.com/lesson/mastery-embedded-conditional
Also a lesson on negating conditionals:
http://7sage.com/lesson/advanced-negate-all-statements/
Okay, that's all. Please carry on!
So... just to clarify:
If we're starting out with "if someone tells the same lie to two different people, then neither of those lied to is owed an apology unless both are,"
I'd have diagrammed it like this:
Tells same lie to both → (~Both owed apol → ~1 owed apol and ~2 owed apol)
Getting rid of the embedded conditional (i.e., taking out the parentheses) yields:
Tells same lie to both and ~Both owed apol → ~1 owed apol and ~2 owed apol
So I get the contrapositive as being:
1 owed apol. or 2 owed apol → ~Tells same lie to both or Both owed apol
If this looks okay, I guess I'm not sure where negating an 'all statement' (the 2nd referenced video lesson) would come into play?
Could someone help me understand this?